RELATION BETWEEN MCKINSEY 7-S FRAMEWORK AND EIGHT BASIC PRINCIPLES - Pongkittiisara, Tanaroj; Thongpikul, Suriyan; Raidee, Nikorn (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2024)
Business competition has increasingly caused organizations to face problems. Management must understand organizations in order to lead to continuous organizational development. The objectives of this research paper were 1) to study the content for the concept of the McKinsey 7-S Framework and Eight Basic Principles, and 2) to study the relationship between the concept of the McKinsey 7-S Framework and Eight Basic Principles. This research used a mixed-methods approach by adopting a quantitative and qualitative paradigm. A questionnaire was used as the data collection tool. The sample consisted of 419 industry representatives in the eastern region. Qualitative data were obtained from discussions with 15 experts using data analysis descriptive statistics, including frequency, percentage, mean, and standard deviation, as well as exploratory factor analysis. According to the research findings, the majority of the respondents were males between the ages of 30-40 years. Most had an educational level at the Bachelor's degree, held manager positions, and had worked for 10-20 years at large business organizations. The concept of the relation to McKinsey 7-S was at a high level overall (𝒙̅ = 4.21). For the relation between McKinsey 7-S, the 15 experts (100%) agreed that there was a relationship with the following aspects: 1) Systems and operating methods are related to practice focus, 2) strategy is related to customer proximity and business expertise, 3) staff are related to freedom of work and ownership, 4) style is closely related to work experience, 5) shared values are related to belief in values, 6) structure is related to the structure that has a simple form and limited administrative personnel, and 7) skill is related to being strict and lenient with employees at the same time. Executives should be able to understand the principles of organizational management to be used as a basis for management,...